Deficient Notch signaling associated with neurogenic pecanex is compensated for by the unfolded protein response in Drosophila. - Yamakawa, T.; Yamada, K.; Sasamura, T.; Nakazawa, N.; Kanai, M.; Suzuki, E.; Fortini, M.E.; Matsuno, K. (Development, 2012)
The Notch (N) signaling machinery is evolutionarily conserved and regulates a broad spectrum of cell-specification events, through local cell-cell communication. pecanex (pcx) encodes a multi-pass transmembrane protein of unknown function, widely found from Drosophila to humans. The zygotic and maternal loss of pcx in Drosophila causes a neurogenic phenotype (hyperplasia of the embryonic nervous system), suggesting that pcx might be involved in N signaling. Here, we established that Pcx is a component of the N-signaling pathway. Pcx was required upstream of the membrane-tethered and the nuclear forms of activated N, probably in N signal-receiving cells, suggesting that pcx is required prior to or during the activation of N. pcx overexpression revealed that Pcx resides in the endoplasmic reticulum (ER). Disruption of pcx function resulted in enlargement of the ER that was not attributable to the reduced N signaling activity. In addition, hyper-induction of the unfolded protein response (UPR) by the expression of activated Xbp1 or dominant-negative Heat shock protein cognate 3 suppressed the neurogenic phenotype and ER enlargement caused by the absence of pcx. A similar suppression of these phenotypes was induced by overexpression of O-fucosyltransferase 1, an N-specific chaperone. Taking these results together, we speculate that the reduction in N signaling in embryos lacking pcx function might be attributable to defective ER functions, which are compensated for by upregulation of the UPR and possibly by enhancement of N folding. Our results indicate that the ER plays a previously unrecognized role in N signaling and that this ER function depends on pcx activity.